2021
DOI: 10.3390/children8100901
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Physical Self-Concept, Physical Activity and Mediterranean Diet in Adolescents from the Province of Granada

Abstract: The aim of the present research was to analyse the relationships among physical self-concept, physical activity engagement and Mediterranean diet adherence in a sample of 1650 secondary school students from the province of Granada. The study design was descriptive–exploratory, cross-sectional and ex post facto. Measurements were taken from a single group. The PSQ, PAQ-A and KIDMED questionnaires were used to measure diet quality. Results showed the presence of a positive relationship among all dimensions of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In terms of physical self-concept, participants with a high adherence to the Mediterranean diet showed higher scores. These results were similar to those found by Zurita-Ortega et al [ 39 ], Pérez-Marmol et al [ 40 ], and Padial-Ruz et al [ 41 ], stating that young people who engage in regular physical activity tend to consume a nutritious and healthy diet, which has a positive impact on sports performance, as well as on body image and well-being.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of physical self-concept, participants with a high adherence to the Mediterranean diet showed higher scores. These results were similar to those found by Zurita-Ortega et al [ 39 ], Pérez-Marmol et al [ 40 ], and Padial-Ruz et al [ 41 ], stating that young people who engage in regular physical activity tend to consume a nutritious and healthy diet, which has a positive impact on sports performance, as well as on body image and well-being.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, PA levels were associated with PSC. A previous study also reported that PA was positively related to PSC in schoolchildren [38]. Likewise, a systematic review with a meta-analysis reported that PA interventions were linked to higher selfconcept in children and adolescents; the authors therefore indicated that PA at school should be increased to promote psychological well-being [74].…”
Section: Discussionmentioning
confidence: 89%
“…Likewise, it has been reported that having low PSC impact the risk of having low levels of PA, bad MD adherence and poor life satisfaction in adolescents [37]. Better PA levels and less ST adherence could impact positively the PSC [38,39] According with the previous evidence, we hypothesized that PSC are linked to wellbeing, physical fitness and lifestyle at the school age. However, there is little information regarding PSC related to lifestyle parameters that include ST and nutritional level markers such as MD adherence in Chilean children.…”
Section: Introductionmentioning
confidence: 81%
“…A positive link is observed between emotional intelligence and Mediterranean Diet adherence. The study by Pérez-Mármol et al [ 41 ] affirms that a healthy diet together with an active lifestyle brings benefits in self-concept, with improvements in the physical and emotional areas of young people.…”
Section: Discussionmentioning
confidence: 99%